A study on the linguistic features of verbs in the process of saying in english and vietnamese newpapers - Đỗ,Thị Phương Dung. (2016)
English is important language used in many countries in all over the world. The importance of English is increasingly being asserted. Today, English is no longer limited to the extent a subject that has gradually become everyday tools of many young people. It is an official and international language. Besides, verb is also important in English, specially, the verbal verb in verbal process. Verbal process verbs play a very important in any language‟s lexicon simply because they actually express the mean of communication, performing the interactional function of the language either directly or indirectly. Thus, the detailed treatment of the verbs belonging to this group is very necessary, hence an important task in the present research paper. To use English exactly is not easy. To understand English in practice and in theory is more difficult; therefore, through the title of my thesis, I found some semantic and syntactic features of verbal verbs in verbal process in English and Vietnamese newspapers. This will help me and others involved to use the verb in particular and English in general. Consequently, the paper also suggests certain implications for the teaching, learning and translating the language materials in use in English and Vietnamese. This is a small category but important. I do this research with the hope that I will understand more about the verbal verb which is used in English and Vietnamese newspapers in verbal process.